ChemInform Abstract: Fast and Complete Transimination of N—H Imines into O‐Alkyl Oximes. Issue 50 (December 2015) - Jeon, Mina; Gupta, Sreya; Im, Young‐Woong; Rhee, Young Ho; Park, Jaiwook
Abstract: The process requires 0.6 equiv.